Evidence based dentistry: Relevance and general concepts - Viteri-García, Andrés (2018)
The Evidence-Based Dentistry (EBD) is a worldwide-recognized concept in the health sciences. It seeks to make clinical decisions based on reliable data from well-conducted researches, which with professional’s experience and patient’s preferences become the best option that can be offered to them. The aim of this review is to summarize the principles of EBD. Hand search of relevant literature was made, OBE concepts and principles are shown as well as examples of the formulation of the PICO question, the search and critical appraisal of information, and the application of that knowledge to ou r patients. It is concluded that the EBD allows the use of the best scientific evidence without leaving aside the experience, professional judgment and patient’s preferences in the decision-making of the daily dentistry practice.